Biodiesel production: a mini review - Nabeel Adedapo, Adeyemi; Mohiuddin, A. K. M.; Jameel, Ahmed Tariq (Asian Institute of Technology Regional Energy Resources Information Center (RERIC), 2011)
The challenges faced in production of biodiesel from edible and non-edible oils via the transesterification process are discussed. Identified process parameters such as level of FFA, moisture content, Fatty acid composition varies for both edible and non-edible oil affects product quality, as a result, the process continues to be modified using competitive alternative methods. Resources and process limitations are reviewed in this paper and in view of current state of the art processes, technical successes and limitations of biodiesel production from plant and animal fats and oils are compared based on reaction conditions and product formation/purification methods. Furthermore,the paper recommends a combination of production systems to overcome the inherent technical limitations in biodiesel production.